Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Compositional and physical properties of skim milk and whey protein concentrate powders prepared from milk of cows fed perennial ryegrass or total mixed ration - Jonathan B. Magan; Tom F. O'Callaghan; Alan L. Kelly; Noel A. McCarthy (International Dairy Journal, 2026)

RT-PCR assay development of ITS and toxin gene regions of, Aetokthonos hydrillicola, a known epiphyte of the invasive species Hydrilla verticillata - Theresa K. Hattenrath; Erika Klar; Katherine C. Callaghan; Madelyn Caldwell; Christopher Tucker; Catherine A. McGlynn; Susan B. Wilde (Harmful Algae, 2026)

Rare cyanobacteria drive nitrogen-fixation and cyanotoxin production in an Aphanizomenon-dominated bloom - Kaela E. Natwora; Adam J. Heathcote; Mark B. Edlund; Shane E. Bowe; Benjamin J. Kramer; Jake D. Callaghan; Cody S. Sheik (Harmful Algae, 2025)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Impact of particulate nitrate photolysis on air quality over the Northern Hemisphere - Golam Sarwar; Christian Hogrefe; Barron H. Henderson; Rohit Mathur; Robert Gilliam; Anna B. Callaghan; James Lee; Lucy J. Carpenter (Science of The Total Environment, 2024)

Multi‐taxon biodiversity responses to the 2019–2020 Australian megafires - Simon B. Z. Gorta; Corey T. Callaghan; Fabrice Samonte; Mark K. J. Ooi; Thomas Mesaglio; Shawn W. Laffan; Will K. Cornwell (Global Change Biology, 2023)
Conditions conducive to fires are becoming increasingly common and widespread under climate change. Recent fire events across the globe have occurred over unprecedented scales, affecting a diverse array of species and habitats. Understanding biodiversity responses to such fires is critical for conservation. Quantifying post‐fire recovery is problematic across taxa, from insects to plants to vertebrates, especially at large geographic scales. Novel datasets can address this challenge. We use presence‐only citizen science data from iNaturalist, collected before and after the 2019–2020 megafires in burnt and unburnt regions of eastern Australia, to quantify the effect of post‐fire diversity responses, up to 18 months post‐fire. The geographic, temporal, and taxonomic sampling of this dataset was large, but sampling effort and species discoverability were unevenly spread. We used rarefaction and prediction (iNEXT) with which we controlled sampling completeness among treatments, to estimate diversity indices (Hill numbers: q = 0–2) among nine broad taxon groupings and seven habitats, including 3885 species. We estimated an increase in species diversity up to 18 months after the 2019–2020 Australian megafires in regions which were burnt, compared to before the fires in burnt and unburnt regions. Diversity estimates in dry sclerophyll forest matched and likely drove this overall increase post‐fire, while no taxon groupings showed clear increases inconsistent with both control treatments post‐fire. Compared to unburnt regions, overall diversity across all taxon groupings and habitats greatly decreased in areas exposed to extreme fire severity. Post‐fire life histories are complex and species detectability is an important consideration in all post‐fire sampling. We demonstrate how fire characteristics, distinct taxa, and habitat influence biodiversity, as seen in local‐scale datasets. Further integration of large‐scale datasets with small‐scale studies will lead to a more robust understanding of fire recovery.

Using valve gape analysis to compare sensitivity of native Mytilus edulis to invasive Magallana gigas when exposed to heavy metal contamination - David B. Kelleghan; Luke O'Callaghan; Freddie Huggard; Tasman P. Crowe; Paul R. Brooks (Marine Environmental Research, 2023)

Many cameras make light work: opportunistic photographs of rare species in iNaturalist complement structured surveys of reef fish to better understand species richness - Christopher J. Roberts; Adriana Vergés; Corey T. Callaghan; Alistair G. B. Poore (Biodiversity and Conservation, 2022)
Citizen science is on the rise, with growing numbers of initiatives, participants and increasing interest from the broader scientific community. iNaturalist is an example of a successful citizen science platform that enables users to opportunistically capture and share biodiversity observations. Understanding how data from such opportunistic citizen science platforms compare with and complement data from structured surveys will improve their use in future biodiversity research. We compared the opportunistic fish photographs from iNaturalist to those obtained from structured surveys at eight study reefs in Sydney, Australia over twelve years. iNaturalist recorded 1.2 to 5.5 times more fish species than structured surveys resulting in significantly greater annual species richness at half of the reefs, with the remainder showing no significant difference. iNaturalist likely recorded more species due to having simple methods, which allowed for broad participation with substantially more iNaturalist observation events (e.g., dives) than structured surveys over the same period. These results demonstrate the value of opportunistic citizen science platforms for documenting fish species richness, particularly where access and use of the marine environment is common and communities have the time and resources for expensive recreational activities (i.e., underwater photography). The datasets also recorded different species composition with iNaturalist recording many rare, less abundant, or cryptic species while the structured surveys captured many common and abundant species. These results suggest that integrating data from both opportunistic and structured data sources is likely to have the best outcome for future biodiversity monitoring and conservation activities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

An ecological baseline for Laminaria hyperborea forests in western Ireland - Kathryn M. Schoenrock; Rory O'Callaghan; Tony O'Callaghan; Aisha O'Connor; Dagmar B. Stengel (Limnology and Oceanography, 2021)
The biodiversity associated with subtidal Irish kelp forests dominated by Laminaria hyperborea has never been described. To enumerate species assemblages in these ecosystems, subtidal surveys were done throughout the calendar year to investigate species assemblages within kelp forests, composition of benthic communities, species colonizing kelp thalli, recruitment to kelp forests, and habitat recovery processes after canopy clearances. Surveys were further undertaken in maërl beds, sediment‐bottom bays, Serpula vermicularis reefs, and bedrock habitats for comparison. Across all four seasons, kelp forests harbor the richest species assemblages, second only S. vermicularis reefs in diversity, with a total of 313 unique species in the habitat (from juvenile recruits to mature macrofauna). Peak diversity in kelp forests occurred in summer and echinoderms were one of the most abundant groups, though urchins never reach densities that would threaten over‐grazing. The thalli of L. hyperborea are diverse habitats harboring many deposit feeders, filter feeders, and marine macroalgae. Epibiotic communities become more diverse with age of kelp, culminating in a maximum of 1660 individuals on stipes and 949 on holdfasts. Recruitment of crustaceans, echinoderms, and worms was high in kelp forests, but recruitment of common Irish fish could not be monitored because of unique life history stage. Habitat establishment took over a year on artificial substrata which were colonized by macroalgae and dense canopy cover inhibited growth of juvenile sporophytes. This descriptive study represents an essential baseline for kelp forest biodiversity in Ireland.

Urban tolerance of birds changes throughout the full annual cycle - Corey T. Callaghan; William K. Cornwell; Alistair G. B. Poore; Yanina Benedetti; Federico Morelli (Journal of Biogeography, 2021)
Aim As urban areas continue to expand, it is increasingly important to quantify species‐specific responses to urban environments, and how these change across the full annual cycle. Our objective was to quantify urban tolerance for North American birds across the time. We tested (a) whether intra‐annual variability of urban tolerance differed between migrants and residents and (b) whether intra‐annual variability of urban tolerance was phylogenetically conserved. We then assessed how the relationship between ecological and life history traits and urban tolerance differed both across the year and between migrants and residents. Location North America. Taxon Birds. Methods We integrated a large citizen science dataset of observations for 237 bird species, remotely sensed VIIRS night‐time lights data, and trait data on each species. We estimate, for each species and each month of the year, a continuous measure of urban tolerance (i.e. the median of their distribution of observations across an urbanization gradient). We then use phylogenetic linear models to assess the relationship between this measure of urban tolerance and various life history and ecological traits. Results There was a distinct drop in the overall urban tolerance scores corresponding with the breeding period; this pattern was more pronounced for migrants compared to residents. Migrants also had greater intra‐annual variability than resident species. We also found that the strength of the relationships between ecological and life history traits and urban tolerance was highly seasonal for most traits considered, and some divergent patterns were noted between migrants and residents. Main conclusions The urban tolerance of birds greatly changed throughout the annual cycle, with different patterns for migrants and residents. Compared to residents, migrants showed more intra‐annual variability of urban tolerance with a drop in the average urban tolerance score during the breeding season. Together, our results suggest that urban tolerance is a function of both species and season, and they highlight the importance of considering the dynamic nature of birds' use of urban ecosystems throughout the full annual cycle.

How to build a biodiverse city: environmental determinants of bird diversity within and among 1581 cities - Corey T. Callaghan; Alistair G. B. Poore; Richard E. Major; William K. Cornwell; John H. Wilshire; Mitchell B. Lyons (Biodiversity and Conservation, 2021)

Citizen science data accurately predicts expert-derived species richness at a continental scale when sampling thresholds are met - Corey T. Callaghan; J. Dale Roberts; Alistair G. B. Poore; Ross A. Alford; Hal Cogger; Jodi J. L. Rowley (Biodiversity and Conservation, 2020)

Quantitation and chemical coding of enteroendocrine cell populations in the human jejunum - Therese E Fazio Coles; Linda J Fothergill; Billie Hunne; Mehrdad Nikfarjam; Adam Testro; Brid Callaghan; Rachel M McQuade; John B Furness (Cell and Tissue Research, 2020)

Relationships of endocrine cells to each other and to other cell types in the human gastric fundus and corpus - Josiane Fakhry; Martin J. Stebbing; Billie Hunne; Yulia Bayguinov; Sean M. Ward; Kent C. Sasse; Brid Callaghan; Rachel M. McQuade; John B. Furness (Cell and Tissue Research, 2019)

Regulation of biosimilar medicines and current perspectives on interchangeability and policy - J. O’Callaghan; S. P. Barry; M. Bermingham; J. M. Morris; B. T. Griffin (European Journal of Clinical Pharmacology, 2019)

Distribution and characterisation of CCK containing enteroendocrine cells of the mouse small and large intestine - Josiane Fakhry; Joyce Wang; Patricia Martins; Linda J. Fothergill; Billie Hunne; Pierre Prieur; Arthur Shulkes; Jens F. Rehfeld; Brid Callaghan; John B Furness (Cell and Tissue Research, 2017)

Analysis of enteroendocrine cell populations in the human colon - Patricia Martins; Josiane Fakhry; Enio Chaves de Oliveira; Billie Hunne; Linda J. Fothergill; Mitchell Ringuet; Débora d’Ávila Reis; Jens F. Rehfeld; Brid Callaghan; John B. Furness (Cell and Tissue Research, 2017)

The chemical coding of 5-hydroxytryptamine containing enteroendocrine cells in the mouse gastrointestinal tract - Yohan Reynaud; Josiane Fakhry; Linda Fothergill; Brid Callaghan; Mitchell Ringuet; Billie Hunne; David M. Bravo; John B. Furness (Cell and Tissue Research, 2016)

Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study - Kate H. Orwin; Bryan A. Stevenson; Simeon J. Smaill; Miko U. F. Kirschbaum; Ian A. Dickie; Brent E. Clothier; Loretta G. Garrett; Tony J. van der Weerden; Michael H. Beare; Denis Curtin; Cecile A. M. de Klein; Michael B. Dodd; et al. (Global Change Biology, 2015)
Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.

Functional profile of a novel modulator of serotonin, dopamine, and glutamate neurotransmission - Gretchen L. Snyder; Kimberly E. Vanover; Hongwen Zhu; Diane B. Miller; James P. O’Callaghan; John Tomesch; Peng Li; Qiang Zhang; Vaishnav Krishnan; Joseph P. Hendrick; Eric J. Nestler; Robert E. Davis; et al. (Psychopharmacology, 2015)

Differences in hormone localisation patterns of K and L type enteroendocrine cells in the mouse and pig small intestine and colon - Hyun-Jung Cho; Samin Kosari; Billie Hunne; Brid Callaghan; Leni R. Rivera; David M. Bravo; John B. Furness (Cell and Tissue Research, 2015)

Salvelinus namaycush spawning substratum attracts egg predators and opportunists through chemosensory cues - B. A. Wasylenko; D. T. Callaghan; P. J. Blanchfield; G. G. Pyle (Journal of Fish Biology, 2014)
Two separate field experiments were conducted in a series of small boreal lakes to test for the attraction of egg predators to lake trout Salvelinus namaycush spawning shoals and subsequently to determine whether chemosensory cues attract egg predators to these sites. In the first experiment, minnow traps set on spawning sites captured significantly more egg predators than those set on structurally similar non‐spawning sites. Captures of slimy sculpin Cottus cognatus , common shiner Luxilus cornutus , blacknose shiner Notropis heterolepis and virile crayfish Orconectes virilis were more than double on spawning sites relative to non‐spawning sites for the two study lakes. To test whether chemosensory cues could attract egg predators to S. namaycush spawning sites, paired minnow traps were placed on eight to 10 sites in each of the three study lakes; one trap contained visually concealed S. namaycush spawning substratum and the other with visually concealed non‐spawning substratum. Traps containing spawning substratum consistently captured more fish and had higher mean daily catches than those that contained non‐spawning substratum. The combined results demonstrate a greater prevalence of egg predators on S. namaycush spawning shoals that appears to be the result of chemosensory attraction to spawning substratum.

Identification of enteroendocrine cells that express TRPA1 channels in the mouse intestine - Hyun-Jung Cho; Brid Callaghan; Romke Bron; David M. Bravo; John B. Furness (Cell and Tissue Research, 2014)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

Mild Clinical and Biochemical Phenotype in Two Patients with PMM2-CDG (Congenital Disorder of Glycosylation Ia) - M. Casado; M. M. O’Callaghan; R. Montero; C. Pérez-Cerda; B. Pérez; P. Briones; E. Quintana; J. Muchart; A. Aracil; M. Pineda; R. Artuch (The Cerebellum, 2012)

Identification of neurons that express ghrelin receptors in autonomic pathways originating from the spinal cord - John B. Furness; Hyun-Jung Cho; Billie Hunne; Haruko Hirayama; Brid P. Callaghan; Alan E. Lomax; James A. Brock (Cell and Tissue Research, 2012)

The genome sequence of Desulfatibacillum alkenivorans AK‐01: a blueprint for anaerobic alkane oxidation - A. V. Callaghan; B. E. L. Morris; I. A. C. Pereira; M. J. McInerney; R. N. Austin; J. T. Groves; J. J. Kukor; J. M. Suflita; L. Y. Young; G. J. Zylstra; B. Wawrik (Environmental Microbiology, 2012)
Summary Desulfatibacillum alkenivorans AK‐01 serves as a model organism for anaerobic alkane biodegradation because of its distinctive biochemistry and metabolic versatility. The D. alkenivorans genome provides a blueprint for understanding the genetic systems involved in alkane metabolism including substrate activation, CoA ligation, carbon‐skeleton rearrangement and decarboxylation. Genomic analysis suggested a route to regenerate the fumarate needed for alkane activation via methylmalonyl‐CoA and predicted the capability for syntrophic alkane metabolism, which was experimentally verified. Pathways involved in the oxidation of alkanes, alcohols, organic acids and n ‐saturated fatty acids coupled to sulfate reduction and the ability to grow chemolithoautotrophically were predicted. A complement of genes for motility and oxygen detoxification suggests that D. alkenivorans may be physiologically adapted to a wide range of environmental conditions. The D. alkenivorans genome serves as a platform for further study of anaerobic, hydrocarbon‐oxidizing microorganisms and their roles in bioremediation, energy recovery and global carbon cycling.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Variability and decline in the number of severe tropical cyclones making land-fall over eastern Australia since the late nineteenth century - Jeff Callaghan; Scott B. Power (Climate Dynamics, 2011)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Complementing structural information of modular proteins with small angle neutron scattering and contrast variation - J. G. Grossmann; A. J. Callaghan; M. J. Marcaida; B. F. Luisi; F. H. Alcock; K. Tokatlidis; M. Moulin; M. Haertlein; P. Timmins (European Biophysics Journal, 2008)

Complementing structural information of modular proteins with small angle neutron scattering and contrast variation - J. G. Grossmann; A. J. Callaghan; M. J. Marcaida; B. F. Luisi; F. H. Alcock; K. Tokatlidis (European Biophysics Journal, 2008)

A mathematical model of fatigue in skeletal muscle force contraction - Paul R. Shorten; Paul O’Callaghan; John B. Davidson; Tanya K. Soboleva (Journal of Muscle Research and Cell Motility, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Nucleocapsid gene variability reveals two subgroups of Lettuce necrotic yellows virus - B. Callaghan; R. G. Dietzgen (Archives of Virology, 2005)

Brain concentrations of d-MDMA are increased after stress - Elizabeth Anne Johnson; James P. O’Callaghan; Diane B. Miller (Psychopharmacology, 2004)

Plant virus surveys on the island of New Guinea and adjacent regions of northern Australia - R. I. Davis; J. E. Thomas; L. A. McMichael; R. G. Dietzgen; B. Callaghan; A. P. James; T. G. Gunua; S. Rahamma (Australasian Plant Pathology, 2002)

Relative potency of controlled-release oxycodone and controlled-release morphine in a postoperative pain model - G. B. Curtis; G. H. Johnson; P. Clark; R. Taylor; J. Brown; R. O'Callaghan; M. Shi; P. G. Lacouture (European Journal of Clinical Pharmacology, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

The economic mineral potential of the mid-Proterozoic Waterberg Group, northwestern Kaapvaal craton, South Africa - P. G. Eriksson; B. F. F. Reczko; C. C. Callaghan (Mineralium Deposita, 1997)